2022
DOI: 10.1021/acs.jpca.2c06564
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Key Properties of the Pyrolysis of Methyl, Ethyl, and Dimethyl Dioxolane Isomers

Abstract: Cyclic acetals are considered as carbon-neutral fuels that can be produced from biomass and renewable electricity. Recent investigations on 1,3-dioxolane, a five-membered cyclic acetal, revealed that unimolecular decomposition through H-atom migration within the ring governs thermal decomposition. For methyl-and ethyl-substituted dioxolane compounds, very limited information on thermodynamic, transport, bond dissociation, and thermal decomposition properties is available. The present study remedies this lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…Accordingly, their pyrolysis and oxidation have only recently been studied. Döntgen et al investigated the unimolecular decomposition of 1,3-dioxolane and found major influences of H atom ring migration; their theoretical study also includes combustion-related properties of methyl- and ethyl-substituted dioxolane compounds for which such information was largely lacking . Hellmuth et al performed an experimental and numerical study of the combustion of 1,3-dioxolane and 1,3-dioxane, five- and six-membered cyclic compounds of similar structure, comparing two representative biohybrid fuels .…”
Section: Fuels and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, their pyrolysis and oxidation have only recently been studied. Döntgen et al investigated the unimolecular decomposition of 1,3-dioxolane and found major influences of H atom ring migration; their theoretical study also includes combustion-related properties of methyl- and ethyl-substituted dioxolane compounds for which such information was largely lacking . Hellmuth et al performed an experimental and numerical study of the combustion of 1,3-dioxolane and 1,3-dioxane, five- and six-membered cyclic compounds of similar structure, comparing two representative biohybrid fuels .…”
Section: Fuels and Mechanismsmentioning
confidence: 99%
“…Dontgen et al investigated the unimolecular decomposition of 1,3-dioxolane and found major influences of H atom ring migration; their theoretical study also includes combustion-related properties of methyland ethyl-substituted dioxolane compounds for which such information was largely lacking. 24 Hellmuth et al performed an experimental and numerical study of the combustion of 1,3dioxolane and 1,3-dioxane, five-and six-membered cyclic compounds of similar structure, comparing two representative biohybrid fuels. 25 They combined ignition delay times, laminar flame speeds, and species measurements in different experimental configurations with kinetic model development and analysis to explain differences in reactivity and aromatic species formation.…”
Section: ■ Molecules and Reactionsmentioning
confidence: 99%
“…22 The inclusion of a methyl group adjacent to the oxygen atom in 4-Me DOL molecules introduces steric hindrance, impeding the accessibility of PF 5 to the oxygen atom. 23 Therefore, 4-Me DOL is a stable cyclic ether. To validate the above conclusions, two different solvent systems were prepared: 1 M LiPF 6 in DOL and 1 M LiPF 6 in 4-Me DOL.…”
mentioning
confidence: 99%